EFFECTIVE WAYS OF ASSESSING SPEAKING - Sadullaeva, A.N.; Espolaeva, E. (SCIENCE and SOCIETY, 2017)
The article deals with the problems of assessing speaking and ways of implementation of language skills and other issues etc. While designing the communicative language tests the teacher should pay attention to the issue that tests should be interactive. The of the tasks communicative test should reflect realistic discourse processing activities, texts and tasks should be relevant to learners level.
Keywords: language test; communicative competence; context; assessment criteria; language scoring rubrics; integrated way; receptive and productive skills